Examining Indonesian Consumer Willingness to Adopt Solar PV: The Effect of Green Consumption, Price Value, Social Influence, and Facilitating Conditions - Mathilda, Ancilla; Theodora, Gabriella; Tarigan, Ruth Srininta (International Journal of Social Service and Research, 2024)
Existing research on solar energy in Indonesia often explores the macroeconomic factors influencing the slow adoption of solar photovoltaic (PV) systems. In contrast, this study places a specific emphasis on the individual consumers' inclination to embrace the technology. The primary research objectives involve examining the impact of price value, green consumption value, social influence, and facilitating conditions on behavioral intention. Data were gathered from a final sample of 210 valid respondents through simple random sampling and subsequently analyzed using PLS-SEM. The results indicate that price value, green consumption value, and facilitating conditions significantly and positively contribute to the intention to adopt solar panels. Conversely, social influence plays an insignificant role in the decision-making process. These findings offer valuable insights that can inform policy initiatives and enhance marketing strategies for promoting renewable energy solutions in Indonesia.